THAT MARKED BY TIME - Ushnevych, S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
In the new book by the Carpathian author Stepan Khorob, "In the Echoes of Time", published by the Ivano-Frankivsk publishing house last year, attention is focused on insufficiently clarified problems in the development of Ukrainian and European drama, in particular, the end of the 19th and the beginning of the 20th centuries. In addition, compared to Stepan Khorob's previous books, the pages of the peer-reviewed edition contain studies of various genres, such as sketches, reviews, and memoirs. The latter belongs rather to journalism, or, more precisely, to memoir literature. And yet "In the echoes of time" is perceived, on the one hand, as a literary and art historical material (chapters "Poetic Drama and Film Art" and "On the Theory and History of Drama"), and on the other hand - as sketches for future research (chapter "Sketches "), as literary reviews (section "Literary and critical reasons"), as commemorative signs (section "Memories").